Presenting signs and patient co‐variables in Gaucher disease: outcome of the Gaucher Earlier Diagnosis Consensus (GED‐C) Delphi initiative - Mehta, Atul; Kuter, David J.; Salek, Sam S.; Belmatoug, Nadia; Bembi, Bruno; Bright, Jeremy; vom Dahl, Stephan; Deodato, Federica; Di Rocco, Maja; Göker‐Alpan, Ozlem; Hughes, Derralynn A.; Lukina, Elena A.; et al. (Internal medicine journal, 2019)
Background Gaucher disease (GD) presents with a range of signs and symptoms. Physicians can fail to recognise the early stages of GD owing to a lack of disease awareness, which can lead to significant diagnostic delays and sometimes irreversible but avoidable morbidities. Aim The Gaucher Earlier Diagnosis Consensus (GED‐C) initiative aimed to identify signs and co‐variables considered most indicative of early type 1 and type 3 GD, to help non‐specialists identify ‘at‐risk’ patients who may benefit from diagnostic testing. Methods An anonymous, three‐round Delphi consensus process was deployed among a global panel of 22 specialists in GD (median experience 17.5 years, collectively managing almost 3000 patients). The rounds entailed data gathering, then importance ranking and establishment of consensus, using 5‐point Likert scales and scoring thresholds defined a priori. Results For type 1 disease, seven major signs (splenomegaly, thrombocytopenia, bone‐related manifestations, anaemia, hyperferritinaemia, hepatomegaly and gammopathy) and two major co‐variables (family history of GD and Ashkenazi‐Jewish ancestry) were identified. For type 3 disease, nine major signs (splenomegaly, oculomotor disturbances, thrombocytopenia, epilepsy, anaemia, hepatomegaly, bone pain, motor disturbances and kyphosis) and one major co‐variable (family history of GD) were identified. Lack of disease awareness, overlooking mild early signs and failure to consider GD as a diagnostic differential were considered major barriers to early diagnosis. Conclusion The signs and co‐variables identified in the GED‐C initiative as potentially indicative of early GD will help to guide non‐specialists and raise their index of suspicion in identifying patients potentially suitable for diagnostic testing for GD.